REPRESENTATION OF SOCIAL INEQUALITY IN SNOWPIERCER (2013) DIRECTED BY BONG JOON HO - Anindya, Raissa Talitha; Nurholis, Nurholis (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
ABSTRACT: My research discusses how social issues that occur in society, such as social inequality represented in literary works, film as the genre, Snowpiercer (2013) directed by Korean director, Bong Joon Ho. The background of the research is social issues that are reflected in literary works. The purpose of the research is, to find out and show to the reader, how social inequality and exploitation are represented in Snowpiercer (2013). The research method used in this research is a literary qualitative method, where all the information is collected in various references. The conclusion that can be obtained from this writing is, that social issues such as social inequality and exploitation can be represented through the literary work, film. Snowpiercer (2013) shows that there is an inequality social issue and exploitation which often occurs in real life society.Keywords: Snowpiercer, Social Inequality, Sociology